Trends of E-education in the Context of Cybernetics Laws. (5th December 2015) - Gushchin, Alexander; Divakova, Marina
Abstract: The new educational paradigm – that is, a transition to learning implementing educational technologies, particularly information and communication technologies (ICT) – opens new possibilities of their analysis from the viewpoint of the management laws and from a perspective of cybernetics. The article demonstrates that for the educational technologies management system built using ICT the cybernetics law of requisite variety must be observed. Observance of the law of requisite variety imposes restrictions on the learner's reactions diversity (behavior). The main trends of e-education that are incidental to the necessity of law observance have been detected. Trend one is the reduction of the courses length and scope when switching to the e-learning. Trend two is the necessity to simulate the learner's behavior. Trend three is the transition to the self-organization model when running courses.